REVIEW DESAIN GEDUNG PELAYANAN TERPADU UNIVERSITAS TRIBHUWANA TUNGGADEWI MALANG DENGAN KONSTRUKSI BAJA - ningrum, Diana; Setya Wijaya, Handika; Umbu Lele, Ardinand Antonius (Jurnal Qua Teknika, 2023)
The application of engineering in the field of civil engineering is growing rapidly, requiring more productivity, creativity, and innovation from structural engineers, especially in the field of structural engineering. To get the optimal cross-sectional dimensions, the magnitude of the forces or loads acting on the structure needs to be analyzed for beams and columns. Under the influence of the working load, the moment bearing capacity will deform evenly throughout the elements. In a flexible structure, the load acting on each structural element needs to be taken into account the moment of deformation. As a design review material, the Tribhuwana Tunggadewi University Integrated Service Building is an integrated service building consisting of 5 floors, which in its main structure uses steel construction, a design review will be conducted, which aims to determine the strength and reliability of the construction. The results of the Review on the Design of the Integrated Service Building, Tribhuwana Tunggadewi University, Malang, are Column(1) steel using the WF profile. 350 . 175 . 7. 11, safe against moments, shear forces, axial forces and buckling or buckling. Column (2) concrete 30 cm x 60 cm is safe against tensile forces, shear forces and axial forces. Block (1) uses WF. 350 .175 . 7. 11, beam (2) uses WF 200 . 100 .5.5 .8 , block (3) uses WF.400.2000.8.13, block (4) uses WF 250 . 125 . 6.9, to the required cross-sectional height and secondary flexural stresses. The floor slab uses 0.75 mm bond with 10 cm concrete and 10 - 200 cm diameter reinforcement (f) which is safe against moments, shear forces and deflections. Connections using Type A-325 bolts with a diameter of 19, safe against tensile forces, shear forces, and bearing forces. Supports using base plates and anchors are safe against tensile forces, shear forces and axial forces.